Dermatological manifestations in Noonan syndrome: a prospective multicentric study of 129 patients positive for mutation. (1st June 2019) - Bessis, D.; Miquel, J.; Bourrat, E.; Chiaverini, C.; Morice‐Picard, F.; Abadie, C.; Manna, F.; Baumann, C.; Best, M.; Blanchet, P.; Bursztejn, A.‐C.; Capri, Y.; et al.
Summary: Background: Data on dermatological manifestations of Noonan syndrome (NS) remain heterogeneous and are based on limited dermatological expertise. Objectives: To describe the dermatological manifestations of NS, compare them with the literature findings, and test for dermatological phenotype–genotype correlations with or without the presence of PTPN11 mutations. Methods: We performed a large 4‐year, prospective, multicentric, collaborative dermatological and genetic study. Results: Overall, 129 patients with NS were enrolled, including 65 patients with PTPN11 ‐NS, 34 patients with PTPN11 ‐NS with multiple lentigines (NSML), and 30 patients with NS who had a mutation other than PTPN11 . Easy bruising was the most frequent dermatological finding in PTPN11 ‐NS, present in 53·8% of patients. Multiple lentigines and café‐au‐lait macules ( n ≥ 3) were present in 94% and 80% of cases of NSML linked to specific mutations of PTPN11, respectively. Atypical forms of NSML could be associated with NS with RAF1 or NRAS mutations. In univariate analysis, patients without a PTPN11 mutation showed (i) a significantly higher frequency of keratinization disorders ( P = 0·001), including keratosis pilaris ( P = 0·005), ulerythema ophryogenes ( P = 0·0001) and palmar and/or plantar hyperkeratosis ( P = 0·06, trend association), and (ii) a significantly higher frequency of scarce scalp hair ( P = 0·035) and scarce or absent eyelashes ( P = 0·06, trend association) than those with PTPN11 mutations. Conclusions: The cutaneous phenotype of NS with a PTPN11 mutation is generally mild and nonspecific, whereas the absence of a PTPN11 mutation is associated with a high frequency of keratinization disorders and hair abnormalities.